2021
DOI: 10.1002/acn3.51286
|View full text |Cite
|
Sign up to set email alerts
|

Gradient of brain mosaic RHEB variants causes a continuum of cortical dysplasia

Abstract: Focal cortical dysplasia (FCD) and hemimegalencephaly (HME) are related malformations with shared etiologies. We report three patients with a spectrum of cortical malformations associated with pathogenic brain‐specific somatic Ras homolog enriched in brain (RHEB) variants. The somatic variant load directly correlated with the size of the malformation, with upregulated mTOR activity confirmed in dysplastic tissues. Laser capture microdissection showed enrichment of RHEB variants in dysmorphic neurons and balloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 10 publications
1
23
0
2
Order By: Relevance
“…Even among somatic variants, the number of DNA fragments that carry the mutation in a sequencing experiment is expected to serve as a surrogate marker for the number of mutated cells in a resected tissue. Accordingly, the so‐called “variant allele fraction gradient” is correlated with a “dysmorphic neuron density gradient,” with the highest variant load detected in the seizure‐onset zone 19,63,64 . Another study reported a synergistic effect of two mosaic variants in mTOR pathway activators ( RPS6 and MTOR ) in a patient with HME 65 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even among somatic variants, the number of DNA fragments that carry the mutation in a sequencing experiment is expected to serve as a surrogate marker for the number of mutated cells in a resected tissue. Accordingly, the so‐called “variant allele fraction gradient” is correlated with a “dysmorphic neuron density gradient,” with the highest variant load detected in the seizure‐onset zone 19,63,64 . Another study reported a synergistic effect of two mosaic variants in mTOR pathway activators ( RPS6 and MTOR ) in a patient with HME 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the so-called "variant allele fraction gradient" is correlated with a "dysmorphic neuron density gradient," with the highest variant load detected in the seizure-onset zone. 19,63,64 Another study reported a synergistic effect of two mosaic variants in mTOR pathway activators (RPS6 and MTOR) in a patient with HME. 65 In all studies, the mosaic fraction of the variants correlated with the lesion type, with greater mosaicism in HME reflecting the earlier timing of occurrence of the mutational event.…”
Section: Mild Malformations Of Cortical Development With Oligodendrog...mentioning
confidence: 99%
“…Single-cell DNA sequencing of brain specimens derived from individuals with HME or FCD showed that the pathogenic somatic variants can occur in both neuronal and non-neuronal lineage, but in small FCD cases they occur specifically in the neuronal lineage only [59]. Using laser capture microdissection, other studies have shown that somatic variants in HME and FCD were most highly enriched in dysmorphic neurons and/or balloon cells compared to other cell types [66,67,77]. Furthermore, the density of dysmorphic neurons and balloons cells in the FCD brain specimens was positively correlated with the level of somatic mutation load [66,67].…”
Section: Pathomechanism Of Fcdii: What Have We Learnt To Date?mentioning
confidence: 99%
“…Using laser capture microdissection, an enriched pool of dysmorphic neurons can be collected for genetic analysis. Indeed, this technique has been successfully applied to target specific cell types from cases with a known somatic variant for downstream analyses [66,67,77]. For detection of an unknown somatic variant (variant discovery) in laser-captured cells, a WES or targeted sequencing approach will likely be required.…”
Section: Detection Of Somatic Mutation: Challenges and Future Directionsmentioning
confidence: 99%
“…Affected individuals display phenotypes ranging from dysplastic megalencephaly, hemimegalencephaly, and focal cortical dysplasia (FCD), as well as comorbidities including hydrocephalus, autism, and intellectual disability (Bast et al, 2006;Blumcke et al, 2011;Stafstrom and Carmant, 2015;Crino, 2016;Mirzaa et al, 2018;Dobyns and Mirzaa, 2019). These Intrinsic Mechanisms Drive PIK3CA-Epilepsy mutations also cause focal epilepsy, representing 25-50% of all cases of intractable (treatment-resistant) epilepsy in children (Bast et al, 2006;Blumcke et al, 2011;Stafstrom and Carmant, 2015;Mirzaa et al, 2018;Kim and Lee, 2019;Rademacher and Eickholt, 2019;Lee et al, 2021). Most current antiseizure drugs target single ion channels because they were developed in acute wild-type rodent seizure models (Kehne et al, 2017;Barker-Haliski and White, 2019;Wilcox et al, 2020).…”
Section: Introductionmentioning
confidence: 99%